Visiting the Big Fresno County Fair - Watkins, Howard::::::::: (1981)
Adam Watkins and Devon Bleile-Kratzer on children's motorcycle ride; Jim Kratzer, Nancy Bleile and Christine Watkins sitting on nearby viewing bench